The occurrence of alcohol/drugs by toxicological examination of selected drivers in Hong Kong. (June 2017) - Cheng, Wing-Chi; Dao, Kwok-Leung
Highlights: Study of fatally injured drivers, drink and drug driving cases were conducted. 18% of deceased drivers detected with alcohol, 9% with drug with/without alcohol. Deceased drivers found with alcohol and drunken drivers identified decreased. Ketamine was the major drug detected in drivers. Single drug use was predominant, an increasing usage of multiple drugs was observed. Abstract: The study is to investigate the extent of alcohol/drug(s) use among selected drivers, i.e. fatally injured drivers from traffic accidents (2006–2015), drink driving (2006–2015) and drug driving (2010–2015) cases, in Hong Kong. Between 2006 and 2015, specimens from a total of 223 fatally injured drivers were received for toxicological examination. Except for one driver, all other drivers with positive findings were male. Alcohol and/or drugs were detected in 60 (27%) cases where alcohol alone was detected in 40 cases (18%) while drugs with/without alcohol were detected in 20 cases (9%). A decreasing trend is observed for cases with blood/breath alcohol concentrations above the prescribed limits in both fatally injured drivers and drivers from drink driving cases in 2006–2015. Out of the 20 cases with positive findings in drugs, 8 of them were found with alcohol in which only one case found at level above the prescribed limit. The frequency of drugs encountered that are known to affect driving in blood is 31, representing an average of about 1.7 drugs per individual. Ketamine was the most frequently detected drug in fatally injured drivers. Sedatives/hypnotics ( i.e. diazepam/nordiazepam, midazolam, 7-aminonimetazepam, 7-aminonitrazepam and zopiclone), morphine/monoacetylmorphine, cocaine/benzoylecgonine, methamphetamine, methadone and codeine were also detected. There has been a sharp increase in the submission of blood/urine specimens for toxicological analysis related to drug driving cases since 2010 with a total of 48 cases received in 2010–2011. With the introduction of legislative amendment of drug driving law since 2012, 154 cases were received in 2012–2015. The positive rates for drug driving cases examined were found to be 90% (43 out of 48 cases) in 2010–2011 and 89% (137 out of 154 cases) in 2012–2015. Drivers with single drug use were more frequently detected (40 cases in 2010–2011 and 82 cases in 2012–2015) than multiple drug use (3 cases in 2010–2011 and 55 cases in 2012–2015) but an increase in the use of more than one drug in driving population is noted. Ketamine was detected in the majority of cases (34 cases in 2010–2011 and 104 cases in 2012–2015). However, drug driving cases in recent years revealed that increase usages of methamphetamine, cocaine and zopiclone were observed. The mean, median and range of ketamine concentrations for 134 blood samples taken from drivers in drug driving cases were 0.34, 0.27, 0.01–1.8 μg/mL respectively.